Transparency and Accountability of State Property Management (BMN) in the Police Logistics System at the East Java Regional Police Logistics Bureau - Nita Febrianti; Fedianty Augustinah; Sedarmayanti Sedarmayanti (Educational Dynamics: International Journal of Education and Social Sciences, 2026)
This research investigates transparency and accountability in the management of state-owned assets (BMN) at the East Java Regional Police's Logistics Bureau as a step toward enhancing effective, adaptive, and integrity-focused governance in police logistics. The research context arises from the growing public call for transparency and accountability in managing state assets, in line with policies for bureaucratic reform and digitalization in the police logistics framework. This study utilized a qualitative descriptive approach involving in-depth interviews, observations in the field, and analysis of documents. The results show that adopting a unified digital system has enhanced the efficiency of asset management, sped up inventory operations, and reduced the risks of asset misuse. Nonetheless, obstacles persist, such as restricted human resource capacity, data alignment problems, and inadequate performance-based assessments. The conversation emphasizes that effective asset management relies on the implementation of adaptive governance, motivation for public service, and precise performance assessment systems. The research indicates that the integration of digital innovation, professional skills, and a robust commitment to public accountability is crucial for creating transparent and sustainable governance in police logistics